Association of Korean Medicine and polypharmacy with fall risk and mortality in older adults with stroke - Lee, Ye-Seul; Jang, Bo-Hyoung; Jeon, Jin Pyeong; Lee, Han-Gyul; Kwon, Seungwon; Jung, Woo-Sang (Frontiers in Pharmacology, 2025)
BackgroundStroke survivors often take multiple medications (polypharmacy), raising concerns about falls and mortality in older adults. This study investigated whether Korean Medicine (KM)—primarily acupuncture—is associated with fall risk and mortality among older adults with stroke and polypharmacy.MethodsA population-based retrospective cohort study using South Korea’s National Health Insurance Service (NHIS) claims database. Adults aged 65 or older with a first stroke in 2015 were included if they had five or more prescribed medications (polypharmacy) or ten or more (hyper-polypharmacy) for at least 270 days. KM users received acupuncture or electroacupuncture (≥3 outpatient visits or ≥1 inpatient stay) within a year of stroke onset. The primary outcome was falls resulting in fracture; the secondary outcome was all-cause mortality—both assessed over 3 years. Propensity score matching balanced demographics, comorbidities, and medication use. Cox proportional hazards and subgroup analyses were conducted. Subgroup and sensitivity analyses explored effect modification.ResultsAmong 25,034 older stroke patients, 10,011 had polypharmacy; of those, 6,809 used KM. After matching, 3,127 KM users were compared with 3,127 non-users. KM users with polypharmacy had a higher rate of falls but lower all-cause mortality than non-users. In hyper-polypharmacy, KM use did not significantly affect falls but was associated with lower mortality. Sensitivity analyses of the unmatched cohort, alternative outcome definitions, and interactions yielded consistent patterns.ConclusionIn older adults with stroke and polypharmacy, KM may improve functional recovery and mobility, potentially increasing falls if balance training is inadequate, yet simultaneously confer survival advantages—perhaps through neuro-immune or systemic effects—irrespective of medication load. Among the more frail hyper-polypharmacy group, KM reduced mortality without altering falls, suggesting that functional gains and competing-risk dynamics differ by medication intensity. Prospective studies with granular functional measures, drug–drug interaction data, and formal competing-risk models are needed to optimize the safe integration of KM into comprehensive stroke care.